An E-learning component for agriculture graduates/post graduates - SUPRIYA, P; YADAV, V K; SINDHU, ANIL KUMAR; JESUDASSAN, VIJAY (The Indian Journal of Agricultural Sciences, 2014)
The agricultural education system has undergone several changes in India from past few decades. There are different courses at graduate and postgraduate level for imparting training to the agriculture students to improve agriculture and allied sectors in our country. An e-learning course has been developed, to make the freshly passed agriculture students and agri business field assistants suitable for agri business industries. This study was conducted in Ikisan Limited, Hyderabad, Andhra Pradesh during 2009 and 2010. To develop the course, surveys were conducted with agriculture students and individuals at managerial level in agri business industries. The gaps that exist between knowledge/skills/attitudes for agriculture students and agri business industries were analyzed. The courses were selected based on gap analysis to assist the students in structuring their career. The content for the courses were obtained from various sources, made into IMS content package using eXe editor and were uploaded in Moodle which is a Learning Management System. The users can access the course online according to their convenience from any place. This module is useful and provides flexibility to working professionals and students who may not attend class room teaching.